The Concept of Unemployment, Its Causes and Its Impacts on Society - Sabira, BENNOUR (Journal of Ecohumanism, 2026)
This paper aims to shed light on the concepts of unemployment and employment, considering them as socio-economic phenomena that require continuous monitoring at various levels. The exacerbation of unemployment, due to neglecting the supply of adequate job opportunities or the absence of a proper plan to address this issue—particularly in developing countries, which are considered young nations—over time contributes to the spread of multiple social problems that may be difficult for planners and decision-makers to control. Among the most prominent of these are poverty, illiteracy, and the deterioration of the health and social conditions of families.